When groups meet : he dynamics of intergroup contact - Pettigrew, Thomas F.; Tropp, Linda R. (Essays in social psychology, 2011)
Presents a comprehensive overview of classic and contemporary work on intergroup contact, combining an extensive meta-analysis of 515 published studies on the topic with the authors' renowned research. This volume provides researchers, students and professionals in social psychology with a sourcebook on intergroup contact